What process can a university follow for open data? The University of Crete case. (28th September 2022) - Tzitzikas, Yannis; Pitikakis, Marios; Giakoumis, Giorgos; Varouha, Kalliopi; Karkanaki, Eleni
All public bodies in Greece, including universities, are obliged to comply with the national legal framework and policy on open data. An emerging concern is how such a big and diverse organisation could develop supporting procedures from an administrative, legal and technical standpoint, that will enhance and expand the level of the provided open data related services. In this paper, we describe our experience, at the University of Crete, for tackling these requirements. In particular, (a) we detail the steps of the process that we followed, (b) we show how an Open Data Catalogue can be exploited also in the first steps of this process, (c) we describe the platform that we selected, how we organised the catalogue and the metadata selection, (d) we describe extensions that were required, (e) we motivate and describe various additional services that we developed and (f) we discuss the current status and possible next steps.